Inaugural Lecture: Mr Bulwark and the Protection of Human Rights - Geiringer, Claudia (Victoria University of Wellington Law Review, 2014)
This is the text of the author’s inaugural lecture as a Professor at the Faculty of Law at Victoria University of Wellington. The author discusses the nature of entrenched bills of rights as a protection mechanism for human rights, particularly focusing on New Zealand and its Bill of Rights Act and the author’s personal journey as a scholar. In the first part of the lecture, the author contrasts her intellectual journeys on constitutions and bills of rights with that of the previous generation, which includes the likes of Sir Kenneth Keith and Sir Geoffrey Palmer. The author suggests that the experience of both generations have been both the same and different due to the political and constitutional climates. In the second part of the lecture, the author argues that we are now in a position to start reaching definitive conclusions about how well the New Zealand Bill of Rights Act 1990 has worked by drawing on her own research. The author concludes that it is time for reform, suggesting that judges need more power to enforce constitutional rights.